Validity confirmation of the Lithuanian form for mental toughness questionnaire among sport schools’ students - Malinauskas, Romualdas; Pocius, Eimantas; Saulius, Tomas; Sniras, Sarunas (Institute of Advanced Engineering and Science, 2025)
Currently, there is a growing interest in measuring mental toughness in Lithuania, but there are no validation measures in place which take contextual factors into account. The scientific problem deals with a limited availability of psychometrically tested mental toughness assessment tools in student populations, specifically within Lithuanian sport schools’ context. Therefore, the purpose is to confirm validity of the Lithuanian form for mental toughness questionnaire (MTQ48) among young sport schools’ participants. The study involved 581 participants aged 15-18 from various Lithuanian basketball sports schools. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) of the questionnaire were performed. Six factors were identified by applying an EFA which explained 63.0% of the total variance. Modelling of the structural equations showed that the six-factor MTQ48 model has a reasonable fit. Analyses of reliability and validity demonstrated a strong internal consistency among the factors. With these suitable reliability and validity characteristics, adapted mental toughness measurement (MTQ48) is suitable for use in research investigating mental toughness among students within Lithuanian sport schools’ contexts.